Resoluções do problema do caixeiro viajante aplicando algoritmos de aproximação, randomização e heurísticas da inteligência artificial com computação paralela - Galuppo, Fabio Razzo (2014)
This work has as its essence the application of techniques collectively called parallel metaheuristic in the context of a Travelling Salesman Problem (TSP), one of the most important problems in combinatorial optimization. The approach of this work contains a compositional proposal that allows the creation of pipelines to address the problem. These techniques extracted from the Parallel Computing associated with the search algorithms of Arti cial Intelligence allow great opportunities for exploring the state space of the problem in question. Using the proposed combinations, good solutions or even optimal solutions will emerge within a satisfactory processing time, allowing its application in real-world problems. It is essential to revisit the existing solutions and provide the best alternatives for the industry to solve the TSP using contemporary computing capabilities and varieties of available equipments. In this work, are included the implementation, analysis and measurement algorithms applied to the referenced context.